Being Good in Third Reisch – a Preliminary Concideration - Grzywacz, Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
Speaking on good in context of Third Reich is a big challenge for a scholar. Realities of German national community – as projected and actualized by Nazis – which based on total exclusion (including physical extermination) of some ethic groups, causes that in order to find something or someone what/who was good there, one needs to refer to statements of the people who took exception to the system and stayed beyond it or on its rim. In this article authoress focuses on Dietrich Bonhoeffer’s diaries, where author depicts years 1936-1942 spent on conspiracy, and chosen documents from Nuremberg trials which reveals enormity of crime made by Nazi system.